The impact of ethical leadership on organizational citizenship behavior in higher education: the contingent role of organizational justice - Mohammad Taamneh; Nader Aljawarneh; Manaf Al-Okaily; Abdallah Taamneh; Ahmad Al-Oqaily (Cogent Business & Management, 2024)
The study examined the relationship between ethical leadership and organizational citizenship, with organizational justice as a moderator. In addition, we investigate how the impact of ethical leadership varies based on the extent to which organizational justice is the prevalent norm within an institution. We examine our proposed model in higher education institutions in northern Jordan and analyze the data using structural equation modeling. The data was gathered from 254 academic staff members employed by private universities. The data set revealed that ethical leadership significantly impacted organizational citizenship behavior in higher education institutions. However, as a moderating variable, organizational justice does not moderate the association between ethical leadership and organizational citizenship behavior (OCB) in Jordanian higher education institutions. Through the moderating role of organizational justice, the authors investigate the effect of ethical leadership on organizational citizenship behavior. This study's findings contribute to the existing body of knowledge by providing evidence from a non-western country, such as Jordan. Based on the findings, the study's theoretical and practical implications, as well as its limitations and recommendations for future research, are discussed.
Keywords: 650; Ethical leadership; organizational citizenship behavior; organizational justice; higher education institutions